Peranan Pendidikan Islam dalam Persoalan LGBT (Lesbian,Gay, Biseksual, Transgender) di Kota Jambi - Muhammad Miptahuttoriq Umar; Hamdi Bin Ishak; Muhd. Nadjib Bin Abdul Kadir; Mohd Izwan Bin Md Yusof (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
LGBT is a social phenomenon that we are regulating in every corner of the country. The LGBT movement was originally present in the 1950s. Which LGBT is present on the basis of human rights (HAM). This study discusses the community, research objectives for research on a healthy generation and moral behavior, which is based on Islamic education, while the research method in this study uses qualitative support. Which discusses about this is used, discussing the reviewer can connect directly with the respondents and get tangible answers from the results of interviews with respondents, while in this study get some satisfying results, that respondents were given further information about the various practices in Islam. LGBT. The conclusion of the study, which is a review of the great for special respondents, about the wider community, that Islamic education can not complement in this life. Whatever the activities, and the role of Islamic education (understanding and practice) cannot be understood